Survival and health related quality of life of patients 12 months following discharge from an adult surgical intensive care unit - Karachi, Farhana (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScPhysio(Interdisciplinary Health Sciences. Physiotherapy))--University of Stellenbosch, 2005.